Genome Size Estimation and Full-Length Transcriptome of Sphingonotus tsinlingensis: Genetic Background of a Drought-Adapted Grasshopper - Zhao, Lu; Wang, Hang; Li, Ping; Sun, Kuo; Guan, De-Long; Xu, Sheng-Quan (Frontiers in Genetics, 2021)
Sphingonotus Fieber, 1852 (Orthoptera: Acrididae), is a grasshopper genus comprising approximately 170 species, all of which prefer dry environments such as deserts, steppes, and stony benchlands. In this study, we aimed to examine the adaptation of grasshopper species to arid environments. The genome size of Sphingonotus tsinlingensis was estimated using flow cytometry, and the first high-quality full-length transcriptome of this species was produced. The genome size of S. tsinlingensis is approximately 12.8 Gb. Based on 146.98 Gb of PacBio sequencing data, 221.47 Mb full-length transcripts were assembled. Among these, 88,693 non-redundant isoforms were identified with an N50 value of 2,726 bp, which was markedly longer than previous grasshopper transcriptome assemblies. In total, 48,502 protein-coding sequences were identified, and 37,569 were annotated using public gene function databases. Moreover, 36,488 simple tandem repeats, 12,765 long non-coding RNAs, and 414 transcription factors were identified. According to gene functions, 61 cytochrome P450 (CYP450) and 66 heat shock protein (HSP) genes, which may be associated with drought adaptation of S. tsinlingensis, were identified. We compared the transcriptomes of S. tsinlingensis and two other grasshopper species which were less tolerant to drought, namely Mongolotettix japonicus and Gomphocerus licenti. We observed the expression of CYP450 and HSP genes in S. tsinlingensis were higher. We produced the first full-length transcriptome of a Sphingonotus species that has an ultra-large genome. The assembly characteristics were better than those of all known grasshopper transcriptomes. This full-length transcriptome may thus be used to understand the genetic background and evolution of grasshoppers.